SPECIES COMPOSITION AND CONSERVATION STATUS OF SHARKS AND RAYS BY-CATCH IN KAKAP RIVER WEST KALIMANTAN - Wolly Candramila; Junardi Junardi; Eka Mardiyanti (Universitas Mataram, 2024)
Production of shark and ray fisheries is still high from various locations in Indonesia. This condition can change the resource stock and its conservation status because it impacts decreasing the number of individuals in the population. Besides the main catch, shark production is also from bycatch, but this data still needs to be widely available. The research aimed to obtain data on the composition and current conservation status of the types of sharks and rays on the mainland of the Kakap River in West Kalimantan from bycatch. The survey method was used in this study by sampling for three months. The guidebook carried out data collection on sharks and rays for the data collection. Identifying samples was carried out directly in the field by collecting, grouping, and measuring the specimens’ body parts, counting the number of individuals, weighing their weight, and determining their sex. The total number of individuals obtained was 1232, consisting of 700 sharks of four species and 532 rays of nine. The species conservation status consists of five vulnerable species; four endangered species; three near threatened species; and one species data deficient. Those species with conservation status still have the risk of extinction in the future.